BASE FORM OF LEXICAL VERBS IN COOKING ARTICLES AND HOW THE HOSPITALITY STUDENTS ARE FAMILIAR WITH THEM - Andi Rizki Fauzi (Universitas Galuh, 2020)
The present study aims to draw up the list of base form of lexical verbs in selected cooking articles and to know whether the fourth semester students majoring in Hospitality have already been familiar with them or not. AntConc, a corpus software, is used to identify the most common verbs in 50 cooking articles taken from Wiki How Web and the quistionnaire were distributed to all the students to give assessment based on the scaling rate provided related to each verbs found in the corpus data. Based on the data analysis, the result showed that from 394 base form of lexical verbs found, there are 174 words got the rating below 5 meaning that the students have ever seen or heard the words but the meanings are vague.It indicates that although the students are in hospitality major, it does not guarantee that they have already known the essential verbs usually used in authentic text. Keywords: Base form of Lexical Verbs, Cooking, Corpus Based Study